2021
DOI: 10.1007/s12029-021-00608-y
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Baseline Volumetric PET/CT Parameters on Treatment Response and Prognosis in Locally Advanced Rectal Cancer Treated with Neoadjuvant Chemoradiotherapy

Abstract: Purpose:To investigate the prognostic effects of baseline volumetric PET/CT parameters including the maximum standard uptake value(SUVmax), metabolic tumor volume(MTV), and tumor lesion glycolysis(TLG) on treatment response and prognosis in locally-advanced rectal cancer(LARC) treated with neoadjuvant chemoradiotherapy(NACRT). Methods:Between 2015 and 2018, 51 patients with LARC treated with NACRT followed by surgery were included in this retrospective study. Patients were divided into 2 groups by tumor regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In another study conducted on 51 patients receiving nCRT for locally advanced disease, Sakin et al . [28] suggested that, from baseline PET CT parameters, MTV could be a predictor of DFS and reported a cutoff value of 12 cm 3 . A study by Lovinfosse et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted on 51 patients receiving nCRT for locally advanced disease, Sakin et al . [28] suggested that, from baseline PET CT parameters, MTV could be a predictor of DFS and reported a cutoff value of 12 cm 3 . A study by Lovinfosse et al .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, SUVmax, MTV and TLG values from the baseline PET parameters of 81 patients receiving nCRT for locally advanced rectal cancer were examined with regard to their value in predicting treatment response, and from these parameters, high baseline TLG values were concluded to be associated with poor DFS outcomes [27]. In another study conducted on 51 patients receiving nCRT for locally advanced disease, Sakin et al [28] suggested that, from baseline PET CT parameters, MTV could be a predictor of DFS and reported a cutoff value of 12 cm 3 . A study by Lovinfosse et al [29] that analyzed the relationship of various clinical and PET CT parameters with survival reported TLG to be an independent predictor of DFS.…”
Section: Discussionmentioning
confidence: 99%